2004
DOI: 10.1093/treephys/24.11.1203
|View full text |Cite
|
Sign up to set email alerts
|

Growth and transpiration of Japanese cedar (Cryptomeria japonica) and Hinoki cypress (Chamaecyparis obtusa) seedlings in response to soil water content

Abstract: To investigate the effects of soil water content on growth and transpiration of Japanese cedar (Cryptomeria japonica D. Don) and Hinoki cypress (Chamaecyparis obtusa (Siebold et Zucc.) Endl.), potted seedlings were grown in well-watered soil (wet treatment) or in drying soil (dry treatment) for 12 weeks. Seedlings in the wet treatment were watered once every 2 or 3 days, whereas seedlings in the dry treatment were watered when soil water content (Theta; m3 m(-3)) reached 0.30, equivalent to a soil matric poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 14 publications
3
36
1
1
Order By: Relevance
“…An increase in root:shoot ratio is a common observation under water stress since drought inhibits growth of the stem more severely than that of the root (Saab et al, 1990), and biomass distribution changes in response to the water content of the soil (Nagakura et al, 2004). In our study, the relationship AB/RW showed a common general tendency for all families, with lower values in those plants subjected to drought stress.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…An increase in root:shoot ratio is a common observation under water stress since drought inhibits growth of the stem more severely than that of the root (Saab et al, 1990), and biomass distribution changes in response to the water content of the soil (Nagakura et al, 2004). In our study, the relationship AB/RW showed a common general tendency for all families, with lower values in those plants subjected to drought stress.…”
Section: Discussionsupporting
confidence: 57%
“…In our study, the relationship AB/RW showed a common general tendency for all families, with lower values in those plants subjected to drought stress. Low values of this parameter are associated with resistance to periods of drought (Nagakura et al, 2004;Villar-Salvador et al, 2004;Yin et al, 2005), indicating a greater investment in root biomass and hence an increased capacity to absorb water from the soil. These changes in the relationship are of great interest in studies of drought tolerance in woody species (Bernier et al, 1995;Farrell et al, 1996) and are regarded as an acclimatization mechanism to avoid dehydration (Guan et al, 2004;Yin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This increase in water use efficiency, found in the gas exchange response to water stress, is attributed to the greater decrease in g s as opposed to A net under glasshouse or field environmental conditions. Others (e.g., [27,37]) have reported a similar water use efficiency response in deciduous and conifer species. Although we were able to achieve more negative Ψ p than the Abrams et al [2] study, Table IV compares our WUE i values to those of other co-occurring species at similar Ψ p values.…”
Section: Variablesmentioning
confidence: 71%
“…Intra-and interspecific differences of E in saplings and mature trees have been well documented in the field and provide a clear picture of microclimate and physiological influences on water loss, including responses to radiation, humidity, air temperature, and soil water deficit (Mott and Parkhurst 1991;Granier et al 2000;Bowden and Bauerle 2008;Herbst et al 2008). In contrast, seedling E has traditionally been observed under manipulated settings, either in greenhouse conditions (Holmgren 2000;Nagakura et al 2004;Baquedano and Castillo 2006) or in the field under an abbreviated range of microclimate variables (Wang et al 2006). A controlled experimental setup provides a method of documenting specific microclimate influences and insures seedling survival, but fails to adequately demonstrate the entire array of meteorological forcings experienced by the seedling in reality.…”
Section: Introductionmentioning
confidence: 99%